Global perspective of ecological risk of plastic pollution on soil microbial communities - Yang, Bing; Wu, Lin; Feng, Wanju; Lin, Qi (Frontiers in Microbiology, 2024)
The impacts of plastic pollution on soil ecosystems have emerged as a significant global environmental concern. The progress in understanding how plastic pollution affects soil microbial communities and ecological functions is essential for addressing this issue effectively. A bibliometric analysis was conducted on the literature from the Web of Science Core Collection database to offer valuable insights into the dynamics and trends in this field. To date, the effects of plastic residues on soil enzymatic activities, microbial biomass, respiration rate, community diversity and functions have been examined, whereas the effects of plastic pollution on soil microbes are still controversial. To include a comprehensive examination of the combined effects of plastic residue properties (Type, element composition, size and age), soil properties (soil texture, pH) at environmentally relevant concentrations with various exposure durations under field conditions in future studies is crucial for a holistic understanding of the impact of plastic pollution on soil ecosystems. Risk assessment of plastic pollution, particularly for nanoplasctics, from the perspective of soil food web and ecosystem multifunctioning is also needed. By addressing critical knowledge gaps, scholars can play a pivotal role in developing strategies to mitigate the ecological risks posed by plastic pollution on soil microorganisms.